Fintech Innovation And IT Infrastructure: Business Implications For Financial Inclusion And Digital Payment Systems - Iqbal Ansari; Kazi Sanwarul Azim; Kiran Bhujel; Suresh Shivram Panchal; Yogesh Sharad Ahirrao (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
This paper explores how FinTech innovations and IT infrastructure can support financial inclusion and improve digital payment systems. Using recent global data - such as India Unified Payments Interface (UPI) which recorded 19.47billion transactions worth 25.08trillion ( USD 293 billion) in July 2025 and the World Bank Findex metrics which show account ownership in developing economies increased in 2022 (71%) compared to 2011 (42%). This paper uses a data-driven mixed-methods design. Quantitative analysis makes use of cross-country time-series data by regressing IT infrastructure readiness (including mobile broadband access indicators, digital public infrastructure measures) on digital payment adoption and financial inclusion indicators. The qualitative insights are based on the case studies of India Stack (including UPI) in India and Africa, which is fast growing in its digital payment ecosystem. Based on key findings, there was a statistically significant positive correlation between the quality of IT infrastructure and the magnitude of digital payment adoption- particularly in ecosystems with digital public infrastructures such as the UPI. This synergy has been able to catalyze quantifiable increases in account penetration and transaction volumes especially to underserved populations. The originality of the study is that all of the technological infrastructure, empirical modeling, and business ramifications were combined in order to shed light on the ways of sustainable financial inclusion. Potential implications of the findings to FinTech firms include strategic application of platform-based models to operate with robust infrastructure, whereas, suggestions to policy-makers include investment in open and interoperable systems and the promotion of regulatory frameworks to support scalable and inclusive digital financial ecosystems.